Making Chicken Nuggets And Chicken Shredded Training For Bukit Manekat Farmer Group Members: Pelatihan Membuat Naget dan Abon Ayam untuk Anggota Kelompok Tani Bukit Manekat - Gemini EM. Malelak; Franky MS. Telupere; I Gusti Ngurah Jelantik; Imanuel Benu; Heri Armadianto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
With many people working in remote places and long working hours, it has an impact on people's consumption patterns. In East Nusa Tenggara (NTT), ready-to-eat food is relatively expensive. The purpose of this activity is to train members of the Bukit Manekat Farmers Group to have the skills to process chicken nuggets and shredded meat, as ready-to-cook/ready-to-eat food for provisions, so that they can save daily cash expenses. Another goal is to diversify family food and it is hoped that in the end this can be used as a family business. The activity methods include socialization, counseling and training. In this activity, chicken nuggets and shredded meat are added with luan bananas, which are typical of Timor Island. Luan bananas are commonly consumed as a substitute for rice. The results of the activity showed an increase in the skills of participants, who previously knew about shredded meat and chicken nuggets products without knowing how to process them, to being able to process them independently. The resulting chicken nuggets and shredded meat have a delicious taste, the physical shape of the nuggets is soft and sandy, while the shredded meat has a fairly smooth texture. The color of the nuggets and shredded meat becomes slightly pale due to the addition of luan bananas.